Lysophosphatidic acid accelerates development of porcine embryos by activating formation of the blastocoel. Issue 1 (15th January 2018) - Shin, Min‐Young; Lee, Seung‐Eun; Son, Yeo‐Jin; Park, Yun‐Gwi; Jeong, Sang‐Gi; Kim, Eun‐Young; Park, Se‐Pill
Abstract : Culture media modifications, including the addition of various factors, are important for the in vitro production of oocytes and embryos. In this study, we investigated the effects of lysophosphatidic acid (LPA) on porcine embryo development. Porcine parthenogenetic embryos were cultured with 0, 0.1, 1, and 10 μM LPA for 7 days, or cultured in basic medium until Day 4 and then treated with LPA from Days 4 to 7. No difference in the in vitro development of embryos cultured with LPA for 7 days was observed. Conversely, rates of blastocyst and over‐expanded blastocyst formation were higher in the 0.1 and 1 µM LPA‐treated versus the other groups of embryos treated from Days 4 to 7. Moreover, formation of early blastocysts occurred earlier and embryo size was larger in LPA‐treated compared to control embryos. Expression of Connexin 43 and gap junction and cell adhesion‐related genes ( GJC1 and CDH1, respectively) was also higher in LPA‐treated compared to control embryos. Despite no difference in the blastocyst total cell number between groups, the apoptotic index was lower in the LPA‐treated group than in the control group; indeed, BCL2L1 (B‐cell lymphoma 2‐like protein 1) expression increased while BAK (Bcl‐2 homologous antagonist killer) decreased in the LPA‐treated group. Thus, addition of LPA to the medium from Days 4 to 7 of culture improves blastocyst formation and aids the development of preimplantation embryos.